Philosophy for Children Meets the Art of Living: A Holistic Approach to an Education for Life - D'Olimpio, Laura; Teschers, Christoph (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2016)
This article explores the meeting of two approaches towards philosophy and education: the philosophy for children (P4C) approach advocated by Lipman and others, and Schmid’s (2000) philosophical concept of Lebenskunst (the art of living). Schmid explores the concept of the beautiful or good life by asking what is necessary for each individual to be able to develop their own art of living and which aspects of life are significant when shaping a good and beautiful life. One aspect of Schmid’s theory is the practical application of philosophy through the notions of Bildung, (self-) refection, prudence and practical wisdom, as well as the requirement for each individual to take responsibility for actively shaping their life as an artwork. In this sense, each person is the artist responsible for living their own beautiful life. We argue that there are some useful parallels between Schmid’s concept of the art of living and P4C, such as the ideal of a holistic philosophy that is “lived”. The pragmatic approach of P4C focuses on the embodied learner who practices critical, caring and creative thinking. Both P4C and Schmid’s theory are reminiscent of the Aristotelian notion of practical wisdom (phronesis), which allows for an approach to an education for life that prepares (young) students to develop their own art of living. We also critically discuss tensions arising between these two concepts.